Populism and Conservative Civil Society - KOUROU, NUR SİNEM (My University, 2018)
There are many components and techniques which are driven by populist radical right parties from top to down. The most important issue can be seen here the populist radical right parties’ linkages with civil society organizations, especially NGOs and social movements. Therefore, a question occurs from this point of view; How do populist radical right parties manifest themselves over civil society organizations? Does the relationship lead to a top-down mobilization? To address these questions, I need to determinate my framework about far-right political extremism and its populist manifestations. Mudde identifies the three defining features of populism which are also experienced and used in its far-right extremism version. These are antiestablishment, authoritarianism, and nativism. This three features are also crucial points to understand situation of civil society organizations and which are mobilized and organized from above. In first place; nativist character of populist radical right parties provide an identification for represented people, they declare who is “us” and who is “other”, and who is “foe”, and who is “enemy”. This distinction is important, because the most important base and appeal is derived from here. Implication of this distinction to the relationship between the party-civil society organizations can be observed like who is going to be mobilized? Secondly, this party family also manifests itself with authoritarian attitude and it mostly relies on a charismatic leader. This perspective and political style also determinate how relationship will constitute between party and civil society organizations. This is going to bring a new understanding on civil society, social movements and NGOs’ literature. How can we identify it as a democratic governance and organization or what? In other words, is there a new way of politics or formation of civil society? Thirdly, the most important onset of the populist radical right parties are derived from their antiestablishment characteristics. In this sense, they represent the voice of ordinary people. From this point, when populist radical right parties destroy established institutions and intellectual ideas in both society and the state level, it generates the new ones to replace them. The civil society organizations are going to be the most important apparatus during this demolition and reconstruction process. The reason why, they are going to use civil society organizations not as an intermediary institution, but also keeping closer to people. In these sense, how should civil society organizations be analyzed; as an objective and non-political institution, or instruments of the populist radical right parties? To develop deeper understanding and apply established research techniques to conduct my research, I will make an empirical study in Turkey and Hungary. With the abovementioned framework, I will analyze the relationship between the governing JDP (Justice and Development Party) and Anatolian Youth Association in Turkey on the one hand and Fidesz and Civic Circle Movement on the other hand. In this sense, 1 aim to put empirical data on my work which is collected by in-depth interviews in Turkish case and secondary material for Hungarian case.
Keywords: Popüler Kültür; Popülizm; Muhafazakarlık; Sivil Toplum; Popular Culture; Populism; Conservatism; Civil Society